Ormianie z Mołdawii, Bukowiny i Siedmiogrodu: Dokumenty i źródła dotyczące związków z Ormianami polskimi w XV–XIX wieku - Marynowski, Marcin (2025)
ARMENIANS OF MOLDOVA, BUKOVINA, AND TRANSYLVANIA DOCUMENTS AND SOURCES ON RELATIONSHIPS WITH POLISH  ARMENIANS IN THE 15TH TO 19TH CENTURIESThe book is a source study showing Armenians from Moldova, Bukovina and Transylvania and their relationship with Polish Armenians. For many years the author collected sources and documents in Romania, the Republic of Moldova, and Ukraine, and supplemented them with selected documents from Poland. The result of the queries is the presented source material showing Armenians from the said area from the 15th to the 19th centuries, with occasional references to the 20th century. The documents were issued in a number of languages: German, Latin, Hungarian, Polish, Romanian (including Cyrillic, the so-called slavonă), Turkish, as well as various Armenian dialects. The book’s subject matter, including the characterization of the sources, selected literature, the development of the Armenian language and the history of Armenians in Moldova and Transylvania, is described in Part I. Part II is largely a thematically divided inventory. It includes sources: documents presented in full, in fragments or regests – the format depended on the original language and the capability of translation. It begins with an excerpt from a Romanian-translated chronicle entitled Kamieniec Podolski albo Kronika Ormian z Polski i Mołdawii [Kamieniec Podolski or Chronicle of the Armenians of Poland and Moldova]. Selected Turkish firmans are published, followed by formal (file) documents. Interesting information about Armenians and Poles from the 1770s comes from the censuses of Moldova. Equally interesting are the descriptions of Chernivtsi and Bukovina after the Austrian occupation. An interesting source from Bukovina is the contents of the ennoblement diploma of Andrzej and Szymon Daszkiewicz. Also noteworthy are texts translated from the Armenian documents collection of the Moldovan History Museum in Iași. The subject of Transylvania is covered in source extracts from private documents, as well as rich photographic material from archives, especially in Cluj, showing Armenian documents and books. Sources relating to Transylvania mainly concern the 18th and 19th centuries, the period after Austria assumed sovereignty over these lands in 1699. There are fragments of official documents mentioning Armenians related to Poles, as evidenced by records of their names. There is also a small number of documents from Maramureş, including those of unknown content. The book ends with a personal index, a list of archives from Romania and Ukraine, supplemented by documents from the Central Archives of Historical Records in Warsaw, and a bibliography. Part III consists of photographs of the sources, taken during the research and included on the CD.
Keywords: Armenians; Poles; Kingdom of Poland; Polish-Lithuanian Commonwealth; Poland; Galicia; Moldova; Bukovina; Transylvania; Maramureş; Romania; documents; ennoblements; genealogy